RELAKSASI PERNAFASAN DENGAN ZIKIR UNTUK MENGURANGI KECEMASAN MAHASISWA - Aulia Syifa; Mufidatul Khairiyah; Setia Asyanti (Universitas Islam Indonesia, 2019)
Breathing relaxation with zikir is one way to give physical and psychological calm to humans.The purpose of this study was to know the effect of breathing relaxation with zikir on decreasing student anxiety. The hypothesis of this study is that there is a significant decrease in anxiety before and after intervention. This research is an experimental study with one group pretest posttest design. Data collection uses the Anxiety Scale. Data analysis used the Wilcoxon technique with the help of the SPSS 15.0 statistical program. The results of the study show that the value of Z count = -2,345 with p = 0,019 (p<0,05). So it can be concluded that there is a significant decrease in anxiety before and after intervention. Based on these results, then breathing relaxation with zikir is able to be one of the solutions to reduce student anxiety.